Mobile Professional Voluntarism and International Development - Ackers, Helen Louise. author. aut Link
XV, 173 p. 13 illus., 11 illus. in color.
Keywords: This book is open access under a CC BY license. This book explores the impact that professional volunteers have on the low resource countries they choose to spend time in. Whilst individual volunteering may be of immediate benefit to individual patients, this intervention may have detrimental effects on local health systems; distorting labour markets, accentuating dependencies and creating opportunities for corruption. Improved volunteer deployment may avoid these risks and present opportunities for sustainable systems change. The empirical research presented in this book stems from a specific volunteering intervention funded by the Tropical Health Education Trust and focused on improving maternal and newborn health in Uganda. However, important opportunities exist for policy transfer to other contexts.